A Saccharomyces cerevisiae RC016-based feed additive reduces liver toxicity, residual aflatoxin B1 levels and positively influences intestinal morphology in broiler chickens fed chronic aflatoxin B1-contaminated diets - Poloni, Valeria Lorena (2020)
The present study was conducted to investigate the ability of Saccharomyces cerevisiae RC016 (Sc)-based feed additive to reduce liver toxicity, residual aflatoxin B1 (AFB1) levels and influence intestinal structure in broiler chickens fed chronic aflatoxin B1-contaminated diets. A total of 100 one-day-old male commercial line (Ross) broiler chickens were divided into 4 treatments, with 5 pens per treatment and 5 broiler chickens per pen. Birds were randomly assigned to 4 treatments, which were namely treatment 1 (T1), control diet (CD); T2, CD + Sc at 1 g/kg; T3, CD + AFB1 at 100 μg/kg; T4, CD + Sc at 1 g/kg + AFB1 at 100 μg/kg. The liver histopathology of broiler chickens fed diets with AFB1 showed diffused microvacuolar fatty degeneration. The addition of Sc showed normal hepatocytes similar to the control. The small intestine villi from AFB1 group showed atrophy, hyperplasia of goblet cells, prominent inflammatory infiltrate and oedema. In contrast, the small intestine villi from birds that received the yeast plus AFB1 showed an absence of inflammatory infiltrate, and atrophy; moreover, a lower number of goblet cells compared to the groups with AFB1 was observed. The morphometric intestine studies showed that a significant decrease (P < 0.05) in the crypt depth values when Sc was applied to AFB1-contaminated diets. Although the intestinal villus height and apparent adsorption area did not show significant differences (P > 0.05), there was a tendency to improve these parameters. The residual levels of AFB1 in livers were significantly reduced (P < 0.05) in the presence of the yeast. The present work demonstrated that the addition of Sc alone or in combination with AFB1 in the broiler chicken diets had a beneficial effect in counteracting the toxic effects of AFB1 in livers besides improving the histomorphometric parameters and modulating the toxic effect of AFB1 in the intestine.